Development of Digital Literacy on Role of the Instagram Platform in Elementary School Students - Manan Manan; Yurfiah Yurfiah; Nuraini Nuraini; Verdianto Verdianto; Kamasiah Kamasiah (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
The purpose of this study is to describe the role of the Instagram platform in increasing digital literacy among grade IV students at Elementary School Country 2 Wameo. Researchers used a qualitative descriptive research method. The subjects of this study were 25 grade IV students. This study uses instruments in collecting data, namely: observation, interviews, and documentation. The data analysis techniques used include: (1) Data reduction (2) Data presentation (3) Conclusion. The results of the study show the role of the Instagram platform in increasin students digital literacy in class IV Elementary School Country 2 Wameo creating interest in students as well as teachers and students being more creative in using technology, making use of up to date learning resources, students' skills in using new media, students obtaining a variety of relevant information. more broadly, and students have experience from the internet so they can improve students' digital literacy skills by fulfilling competencies in the form of technical abilities, critical understanding, and the ability to communicate and participate.